Selection and plasticity both account for interannual variation in life‐history phenology in an annual prairie legume. Issue 2 (10th January 2020) - Nashoba, Amber R.; Kono, Thomas J. Y.
Abstract: As the environment changes, so too must plant communities and populations if they are to persist. Life‐history transitions and their timing are often the traits that are most responsive to changing environmental conditions. To compare the contributions of plasticity and natural selective response to variation in germination and flowering phenology, we performed a quantitative genetic study of phenotypic selection on Chamaecrista fasciculata (Fabaceae) across two consecutive years in a restored tallgrass prairie. The earliest dates of germination and flowering were recorded for two parental cohorts and one progeny cohort in an experimental garden. Environmental differences between years were the largest contributors to phenological variation in this population. In addition, there was substantial heritability for flowering time and statistically significant selection for advancement of flowering. Comparison between a progeny cohort and its preselection parental cohort indicated a change in mean flowering time consistent with the direction of selection. Selection on germination time was weaker than that on flowering time, while environmental effects on germination time were stronger. The response to selection on flowering time was detectable when accounting for the effect of the environment on phenotypic differences, highlighting the importance of controlling for year‐to‐year environmental variation in quantitative genetic studies. Abstract : Our study is a phenotypic selection analysis of total lifetime fitness in a natural selective prairie environment. We compare the predicted and observed phenotypic response, taking care to account for the effect of year‐to‐year variation. We observe a change in mean flowering time that is consistent with the direction of selection when accounting for the effect of the environment, highlighting the importance of controlling for temporal variation in multiyear quantitative genetic studies.